Real-life efficacy and safety of vildagliptin compared with sulfonylureas as add-on to metformin in patients with type 2 diabetes mellitus in Germany. (May 2014) - Göke, R.; Gruenberger, J. B.; Bader, G.; Dworak, M.
Abstract Objective: Metformin is an established first-line treatment for type 2 diabetes mellitus (T2DM) patients, but intensification of oral anti-diabetes therapy is usually required over time. A large observational study of 45, 868 T2DM patients in 27 countries (EDGE) was conducted to compare the effectiveness and safety of vildagliptin as add-on therapy to another oral anti-diabetes drug (OAD) vs other dual OAD combinations. This report presents results from a post-hoc analysis of patients in Germany who received vildagliptin or a sulfonylurea (SU) in combination with metformin. Research design and methods: Patients inadequately controlled with monotherapy became eligible only after the add-on treatment was finalized. Patients included were assigned to receive either vildagliptin or another OAD (SUs, thiazolidinediones, glinides, α-glucosidase inhibitors, or metformin; DPP-4 inhibitors or glucagon-like peptide-1 [GLP-1] mimetics/analogs were excluded). The primary end-point was the proportion of patients achieving a reduction in HbA1c >0.3% without peripheral edema, hypoglycemia, discontinuation due to gastrointestinal event, or weight gain ≥5%. Results: Of 8887 patients enrolled in Germany, 6439 received vildagliptin and 971 received SUs as add-on to metformin. The primary end-point was reached in 34.9% and 29.6% of patients in the vildagliptin and SU groups, respectively, with an unadjusted odds ratio of 1.27 (95% CI = 1.09, 1.47; p = 0.001). HbA1c decreased in both cohorts from baseline (−0.7% with vildagliptin vs −0.5% with SUs), with a mean between-group difference of −0.2% (95% CI = −0.22, −0.09). The number of hypoglycemic events was 4-fold higher in the SU group than in the vildagliptin group (vildagliptin = 0.11%; SU = 0.41%). Conclusions: In a real-life setting, vildagliptin was associated with a numerically greater reduction in HbA1c, less hypoglycemia, and more patients reaching target HbA1c without hypoglycemia or weight gain compared with SUs. Open-label design and under reporting of adverse events are limitations of this post hoc analysis.